1999
DOI: 10.1177/014556139907800814
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Mucociliary Clearance and Nasal and Oral pH in Patients with Insulin-Dependent Diabetes

Abstract: We studied 32 pati ents with insulin-dependent diab etes mellitus to determine how their rate ofmucoc iliary clearance and their levels ofnasal and oral pH compared with those of 10 nondiabetic contro ls and how these rhinologic measurements varied within different subsets ofdiab etic patients. A lthough wefo und very f ew statistically significant differences in all our comparisons, we did fi nd that nasal mucociliary clearance and oral pH levels in the diabetic patients were significant ly differe ntfro m th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
0
6
0
5
Order By: Relevance
“…It also has been shown that patients with diabetes may have decreased mucociliary clearance owing to alkalinized pH values of nasal secretions. 18,19 Sinus congestion triggers the disease process, which leads to obstruction of the sinus ostium and ultimately to an alteration of the microflora of the sinus cavity. If the obstruction fails to resolve, a chronic inflammatory response ensues, which affects the sinus respiratory mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…It also has been shown that patients with diabetes may have decreased mucociliary clearance owing to alkalinized pH values of nasal secretions. 18,19 Sinus congestion triggers the disease process, which leads to obstruction of the sinus ostium and ultimately to an alteration of the microflora of the sinus cavity. If the obstruction fails to resolve, a chronic inflammatory response ensues, which affects the sinus respiratory mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel wiesen Diabetiker in der RMM einen erh ö hten nasalen Widerstand -und zwar gr ö ß er vor als nach Abschwellen [166] -als Ausdruck eines chronischen endonasalen Schwellungszustandes auf. Dieser wird auch durch die mukozili ä re Clearance beg ü nstigt, die in Diabetikern bei ins alkalische verschobenen pH-Werten des Nasensekretes [205] verlangsamt ist [206,207] . Der Gebrauch von Insulin und eine Erkrankungsdauer von mehr als zehn Jahren gehen mit einer weiteren Verschlechterung der mukozili ä ren Clearance einher [205] .…”
Section: Einfl Uss Von Diabetes Mellitus Auf Die Respiratorische Funkunclassified
“…Chronic congestion is also favoured by mucociliary clearance, the latter being reduced in diabetics [205], [206] due to alcalised pH-values of nasal secretions [207]. Insulin-dependent diabetes mellitus and diabetes lasting for more than ten years result in further deterioration of mucociliary clearance [207].…”
Section: Physiology Of Respiratory Mucosamentioning
confidence: 99%